Moscow Rules? 'Red' Unionism and 'Class Against Class' in Britain, Canada, and the United States,1928-1935 - Manley, John (Labour/Le Travailleur, 2005)
Abstract In the still vibrant debate between "traditionalist" and "revisionist" historians of international Communism, the former tend to argue that the key to understanding the Communist experience in any country is recognition of the fundamental subordination of each national party to the will of "Moscow," exercised both directly and through the Communist Internationa! (Comintern), while the latter, though rarely denying the salience of the Moscow connection, suggest that national parties enjoyed a significant degree of autonomy in resisting or adapting Moscow's demands. American revisionists in particular have emphasized the CPUSA's creative engagement with American political culture, seeing this phenomenon even in the period most traditionalists see as the point at which national parties incontrovertibly capitulated to Stalinism — the "Third Period" (1928-35) of "Class Against Class," ultra-leftism, "Social Fascism," and political catastrophe in Germany. Using the surprisingly under-used tool of comparative analysis to evaluate the conception, implementation, evolution, and "liquidation" of the Third Period in the United States, Britain, and Canada, this article offers some succour to the revisionists, but rather more to the traditionalists.